On understanding the nature of interpersonal conflict between coaches and athletes - Wachsmuth, S.; Jowett, S.; Harwood, C. G. (Journal of Sports Sciences, 2018)
Conflict is a part of coach-athlete relationships and should be carefully considered as it can have effects on the quality of coaching and the level of performance. Despite its practical relevance, there is a dearth of research around coach-athlete conflict. Therefore, the current study aimed to explore the characteristics and topics of conflict, as well as coaches and athletes` emotional, cognitive and behavioural experiences during conflict. A total of 22 independent coaches and athletes participated in semi-structured interviews evolving around the nature of interpersonal conflict. After all interviews were transcribed, a deductive-inductive content analysis was conducted. This was guided by the interview schedule as well as the by the conceptual framework of conflict in sport relationships (Wachsmuth, Jowett, & Harwood, 2017). Data were divided into five main categories: Conflict characteristics and conflict topics, as well as conflict cognitions, emotions, and behaviours. Findings highlighted the variety of ways in which participants understood and interpreted interpersonal conflict and how their impressions of conflict influenced its evolving process. Considering the participants` cognitive, emotional and behavioural expressions of conflict, it became apparent that conflict can be described through uncertain, escalating and problem-orientated responses. Practical applications concerning (mal-) adaptive responses to conflict are discussed.